Quality over quantity: an analysis of Afghanistan consumers’ preferences for fruit safety and quality attributes - Joya, Khalid; Ramli, Nurul Nadia; Younisi, Hamidullah; Amin, Mohammad Wasif; Farid, Zabihullah (Elsevier, 2025)
While food safety and quality are of utmost importance for the overall welfare of the world, very little is known about Afghanistan where food insecurity is a significant concern. Afghanistan is confronted with political instability, economic adversity, and environmental issues, resulting in a lack of food. Agriculture serves as the primary economic resource for more than 60 % of the Afghan populace. Ensuring the safety of food is crucial for stabilizing livelihoods and reestablishing the connection between afflicted individuals and their sources of food. Hence, this study aims to ascertain the preferences and willingness of consumers to pay for the quality and safety aspects of grapes. The study was carried out in Kabul, with 410 respondents successfully completing the questionnaires. The study utilized the discrete choice experiment (DCE), and the results indicated that consumers have shown a willingness to pay a higher price for grapes that have superior food safety and quality attributes. In addition, the study found that income, education level, and age are other factors that can influence people's willingness to pay for the quality and safety attributes of grapes. The findings provide essential insights for policymakers and stakeholders in the agricultural sector to improve food safety regulations, targeting an increase in consumer confidence and the competitiveness of local produce in the market.